PENGARUH KOMPRES HANGAT TEMULAWAK TERHADAP NYERI SENDI PADA LANSIA DENGAN OSTEOARTHRITIS - Evi Royani; Elvrinica Christina (LPPM STIKes Mitra Adiguna, 2026)
Elderly people often experience osteoarthritis which causes joint pain and inhibits activity. Warm curcuma compress is a non-pharmacological therapy containing curcuminoids as an anti-inflammatory and analgesic to reduce pain. Objective: To determine the effect of giving curcuma compress on the level of joint pain in elderly people with osteoarthritis at Harapan Kita Social Home in Palembang. Method: This study is a quantitative study with a pre-experimental design using a one group pre-post test design approach. The study was conducted on November 15-22, 2025 with a sample of 24 respondents selected according to the inclusion criteria. Data were collected through pain scale observation sheets before and after the intervention, then analyzed using the Wilcoxon statistical test. Results: The characteristics of the respondents were mostly women (65%) and were in the age range of 60-65 years (75%). Before being given curcuma compress, the average pain scale of respondents was 6.70 (moderate to severe pain). After the intervention, the average pain scale decreased to 3.25 (mild pain). The Wilcoxon test results showed a significant p-value of 0.000 (<0.05). Conclusion: There was a significant effect of curcuma compress therapy on reducing joint pain levels in elderly people with osteoarthritis. This therapy can be used as a safe and effective self-treatment reference for the elderly.